FORMULATION AND IN VITRO CHARACTERIZATION OF THIOCOLCHICOSIDE PRONIOSOMES FOR ORAL DELIVERY - Antil, Deepa; Sharma, Rahul; BHUSHAN, BHARAT (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The main objective of the present study was to develop a controlled release formulation of proniosomes of thiocolchicoside. Methods: The formulations of proniosomes were prepared with thiocolchicoside varying the Span 60 and cholesterol ratio in the range of 4.5:1–1:4.5 using sucrose stearate as carrier by slurry method. The different proniosomal formulations prepared were characterized for micromeritic properties and further %Entrapment efficiency, %Drug content, and loading efficiency were also determined. The best optimized formulation F8 was characterized for particle size distribution, zeta potential, scanning electron microscopy, in vitro dissolution studies, and in vitro release kinetics to determine the release pattern of the drug from the formulation. Further, the formulated proniosomes were subjected to stability studies. Results: The Fourier-transform infrared spectroscopy study showed no interaction between drugs and other excipients. The entrapment efficiency of proniosomes formulations found within the range of 49.71–83.62%. The formulation F8 was characterized for the in vitro dissolution studies which showed drug release 94.30% within 24 h when compared with pure drug. Kinetic analysis of drug release profiles showed that the drug release was followed by Korsmeyer–Peppas model (R2=0.9413) resulted in controlled release. The mean particle size and zeta potential of proniosome derived niosomes were found to be 118.34 nm with polydispersity index 14.9% and −36.8, respectively, and has reasonably good stability characteristics as well. Conclusion: Proniosomal formulation of thiocolchicoside may be used as controlled drug delivery system for oral administration. Hence, proniosomes could act as a promising alternative option for oral drug delivery.